Urgent dental care in the Brazilian public health system: learning lessons from the COVID-19 pandemic for future situations - Heloisa Grehs e Silva; Patrícia Maria Poli Kopper Móra; Luciéli Andréia Zajkowski; Roger Keller Celeste; Roberta Kochenborger Scarparo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This ecological study described the effect of the COVID-19 pandemic and socioeconomic development on the use and profile of urgent dental care (UDC). UDC rates per 100,000 inhabitants before (from March to June 2019) and during (from March to June 2020) the COVID-19 pandemic in 4,062 Brazilian municipalities were compared. Data were collected from official sources. COVID-19 mortality and hospitalization rates were indicative of levels of lockdown and Human Development Index (HDI) indicated socioeconomic development. Multiple logistic regression and relative excess risk due to interaction (RERI) were used for statistical analyses. The Student t-test was used to compare changes in the profile of UDC causes and procedures in the two periods. Lower UDC rates were found in 69.1% of municipalities and were associated with higher HDI (OR = 1.20; 95%CI: 1.01; 1.42). Mortality had OR = 0.88 (95%CI: 0.73; 1.06) for municipalities with HDI < 0.70 and OR = 1.45 (95%CI: 1.07; 1.97) for municipalities with HDI > 0.70. RERI between HDI and COVID-19 was 0.13 (p < 0.05). Municipalities with greater primary health care coverage had a smaller reduction in emergency rates. Endodontic treatment and dental pain were the most frequent factors both before and during the pandemic. The percentage of UDCs due to pain and soft tissue damage, as well as temporary sealing and surgical procedures, increased. Socioeconomic variables affected UDC rates during the most restrictive period of the COVID-19 pandemic and should be considered in the planning of health actions in future emergencies.